ANALISIS MOTIVASI BELAJAR PESERTA DIDIK PADA PASCA PEMBELAJARAN DARING KELAS X AKL 3 MATA PELAJARAN SPREADSHEET (PENGOLAHAN ANGKA) DI SMKN 1 PONTIANAK - Novia Eka Giarti; Bambang Genjik; Okianna Okianna (Universitas Tanjungpura, 2022)
The study aims to find intrinsic and extrinsic laearners’ motives in the post online study of the X AKL 3 class of spreadsheet lessons at SMKN 1 Pontianak. The research methods used are descriptive with qualitative forms of research. The source of this research data is the X AKL 3 class learner and his data consist of interviews with the spreadsheet tuition teacher and the X AKL 3 learner. Research shows the motivation for learning to be student at (1) the desire and the desire to succed the student is pretty good (2) the needs and encouragement in learning are well defined (3) hopes and ideals are categorized as good. The student’s extrinsic motivation on (1) the award learning is categorized quite well (2) the interesting activity of learning is categorized quite well (3) conducive learning is categorized quite well.